Relation Between Intimate Partner Violence During Pregnancy and Postpartum Mother Psychological Wellbeing - Ahmed, Amal Gamal Mohamed; Saeed, Marwa Mostafa; Hussein, Hoda Abdou; Nahas, Heba Galal El (South Eastern European Journal of Public Health, 2024)
Background: Intimate partner violence (IPV) may be physical violence, psychological or sexual abuse by a current or former intimate partner. It is an avoidable global public health problem. IPV in pregnancy, despite being a common problem but remains a neglected condition (1). The severity of violence from a partner during pregnancy was reported to be greater than violence before pregnancy due to possibly change in a couple’s relationship and lifestyle accompanying pregnancy (2).Numerous studies revealed that experiencing IPV during pregnancy negatively affects both mothers and infants during the post- partum period(3).Objectives: to assess prevalence of postpartum depression and anxiety and assess possible relation between partner violence during pregnancy and postpartum psychological health. Design: prospective cohort study Method: This study was carried out on 176 pregnant women attending antenatal care to explore the possible relation between intimate partner violence and postpartum depression and anxiety. The assessment was done during the second trimester by screening the sociodemographic factors, screening of intimate partner violence was done using the Arabic version of the Composite Abuse Scale. Postpartum assessment by screening of maternal depression was done by the Arabic version of the Edinburgh post-partum depression scale, and screening of anxiety using the Arabic version of Perinatal Anxiety Screening Scale. Results: the prevalence of intimate partner violence during pregnancy was 19.3%. Near half of participants suffered from postpartum depressive illness and around one quarter suffered from possible depression. More than half of participants suffered from mild to moderate postpartum anxiety. Partner violence had also significant relation with depression during pregnancy and post-partum with p-value <0.001 for both. Conclusions: intimate partner violence may be a risk factor for postpartum depression and anxiety.so, we should screen for it and learn how to deal with this problem.